1995
DOI: 10.1111/j.1600-0897.1995.tb00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antiendometrial Antibodies in Sera of Patients With Endometriosis by Dual‐Colored, Double‐Labeling Immunohistochemical Method and Western Blot

Abstract: These data show that specific IgG antibodies reactive against endometrial antigens are detectable in sera from some patients with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…21 These include retrograde menstruation, coelomic metaplasia theory, lymphatic and blood vessels disseminating endometrial cells, and another theory that cells from bone marrow circulate and differentiate into endometrial tissue. 31 The presence of serum and peritoneal fluid antiendometrial antibodies (AEA) in patients with E has been well described and correlates with surgically verified E. 29,[32][33][34][35][36][37] The gold standard for detection of E, however, is laparoscopic surgery because E is defined anatomically and clinical reports have correlated the appearance of suspected and biopsied E lesions with pathological confirmation of endometrial glands or stroma located outside the uterus. [22][23][24][25] Thus, E is considered by many to be an autoimmune disease, sharing many characteristics with other autoimmune disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 These include retrograde menstruation, coelomic metaplasia theory, lymphatic and blood vessels disseminating endometrial cells, and another theory that cells from bone marrow circulate and differentiate into endometrial tissue. 31 The presence of serum and peritoneal fluid antiendometrial antibodies (AEA) in patients with E has been well described and correlates with surgically verified E. 29,[32][33][34][35][36][37] The gold standard for detection of E, however, is laparoscopic surgery because E is defined anatomically and clinical reports have correlated the appearance of suspected and biopsied E lesions with pathological confirmation of endometrial glands or stroma located outside the uterus. [22][23][24][25] Thus, E is considered by many to be an autoimmune disease, sharing many characteristics with other autoimmune disorders.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Patients with E concomitantly have other autoimmune disorders. 31 The presence of serum and peritoneal fluid antiendometrial antibodies (AEA) in patients with E has been well described and correlates with surgically verified E. 29,[32][33][34][35][36][37] The gold standard for detection of E, however, is laparoscopic surgery because E is defined anatomically and clinical reports have correlated the appearance of suspected and biopsied E lesions with pathological confirmation of endometrial glands or stroma located outside the uterus. Thus, one can easily see how surgical diagnosis is a gross anatomic diagnosis that does not usually have a paired histological confirmation and thus may have significant false positives and negatives.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the research methodology, we included a total of forty-one eligible case-control studies to investigate the correlation between the presence of autoantibodies and the risk of endometriosis. Eighteen studies were conducted in Europe (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) , eleven in Asia (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) , nine in North America (29,(44)(45)(46)(47)(48)(49)(50)(51) , and four in South America (52)(53)(54)(55) . The basic characteristics of the included studies are listed in Table 1 and Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For women in the early stages of the disease, artificial insemination with ovulation induction may be more effective in increasing the natural conception rate compared to expectant management [60]. A single randomized controlled clinical trial (RCT) of very low size showed a higher clinical pregnancy rate associated with extended GnRH agonist suppression prior to IUI (Kim et al, 1995) [61].…”
Section: Tubal Endometriosismentioning
confidence: 99%